E-Catalogue Utilization Counseling for Small and Medium Enterprises Association in Surakarta City - Kristina Setyowati; Septyanto G. Prakoso; Is Hadri Utomo; Herwan Parwiyanto; Retno Suryawati; Rino A. Nugroho; Priyanto Susiloadi; SA Santoso (Universitas Lancang Kuning, 2023)
The existence of the e-catalog program began to grow rapidly in Indonesia. However, currently, the understanding of SMEs related to the use of e-catalogs is still low. Moreover, currently, most of the consumers and public facilities built have started to use digital technology, so SMEs must be able to integrate their business with technological developments, especially through e-catalogs to make it easier to market their goods and services. The e-catalog is currently aimed at encouraging revenue growth in the SME sector and the government sector to reduce corruption rates related to the procurement of government goods and services. This community service is carried out by providing counseling related to e-catalogs to the Solo UMKM Association (PUS). The results of this counseling show that counseling related to the e-catalog is in accordance with the needs of UMKM players in Surakarta City and answers the concerns of UKM players in Surakarta City regarding how to access and use the e-catalog itself so that it can support the achievement of the government's target of using e-catalogs.